2021
DOI: 10.1590/2317-1545v43251724
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability among jarina palm (Phytelephas macrocarpa Ruíz & Pavón) progenies based on seed, germination and seedling characteristics

Abstract: Jarina is a palm tree from the western Amazon region, whose seeds have characteristics like those of animal ivory, used for making handicrafts. The aim of this work was to evaluate the genetic variability of jarina palm progenies, from seed morphophysiological characteristics, germination and seedling stages. The experimental design adopted was completely randomized, with 15 treatments (progenies), 3 repetitions, and 15 seeds per experimental unit. Thirty-one morphophysiological characteristics of the seed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…According to Rodrigues et al (2015), the biometric characteristics can provide information necessary for the selection of seeds of greater size and mass since these parameters have contributed to greater success in germination and vigor tests of some palm tree species. Ferraz et al (2021) found that morphophysiological characteristics of seeds, germination and seedlings are useful to detect genetic variability among Phytelephas macrocarpa Ruíz & Pavón progenies.…”
Section: Discussionmentioning
confidence: 99%
“…According to Rodrigues et al (2015), the biometric characteristics can provide information necessary for the selection of seeds of greater size and mass since these parameters have contributed to greater success in germination and vigor tests of some palm tree species. Ferraz et al (2021) found that morphophysiological characteristics of seeds, germination and seedlings are useful to detect genetic variability among Phytelephas macrocarpa Ruíz & Pavón progenies.…”
Section: Discussionmentioning
confidence: 99%
“…As the majority of palm species, its propagation is predominantly done by seeds that can germinate a few days after sowing (Luz et al, 2008;Bao et al, 2010), however, they show sensitivity to desiccation in water contents below 20%, with critical content ranging between 10 and 15% (Batista et al, 2016). In this perspective, it is important to understand better the physiology of seeds to assist in their conservation, initial plant development, as well as to evaluate genetic variation in natural populations (Ferraz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%